Into the wild blue yonder : my life in the Air Force - Stein, Allan T., 1924- (Centennial of flight series ;, 2005)
"Allan T. Stein idolized his uncle, a pilot in the Great War. So in 1943, in the midst of the Second World War, he left Texas A & M University for Lackland Air Field to learn to fly. By the time he retired as a lieutenant colonel in 1969, Stein had flown everything from BT-13s and B-24s to B-52s and C-47s. During World War II, he flew missions over China and the Sea of Japan, and by V-J Day, he had participated in eight campaigns and logged 347 hours in combat. Stein later spent one year in Vietnam as operations officer for the 360 TEWS (Tactical Electronic Warfare Squadron), which used refitted C-47s to monitor and locate Vietcong units. He ended his career as inspector general of the Civil Air Patrol." "Stein considers himself to have been an ordinary airman, not a hero. But he was also a seasoned pilot and a conscientious officer with a strong sense of right and wrong. After a young pilot he had certified died in an accident, Stein made it a practice to fail all but the best candidates. He was just as disgusted with the corruption he encountered in the Civil Air Patrol as he was with the tendentious reporters he met in Saigon's Hotel Caravelle." "Although he met his share of cowards and scoundrels, Stein loved to fly and he loved the air force. He was the sort of officer his superiors trusted not to make mistakes, but he was not the sort to rise to high rank. What he offers here is an account of a typical career as an air force officer, complete with its frustrations, moral dilemmas, and the occasional harrowing experience."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved